The halal fashion trends for hijabi community: Ideology and consumption - Nilda Susilawati; Miti Yarmunida; Khairiah Elwardah (Universitas Trunojoyo Madura, 2021)
The research is based on a large enough market potential for the development of the halal fashion industry in Indonesia. The hijab fashion trend is a production target that continues to develop with various technologies and innovations, which encourage the consumption of community groups to use hijab fashion to continue to increase. The study was conducted to determine the purpose of the hijab community in using halal hijab fashion as part of their identity in demonstrating the existence of the hijab group through the ideological and consumption approaches. Qualitative analysis is carried out to determine the ideological emphasis and consumption of the hijab community through open interviews to obtain a clear picture of the social situation. The results show that religious beliefs are the main basis in encouraging the use of hijab and necessity factors.